2019
DOI: 10.1051/matecconf/201925408005
|View full text |Cite
|
Sign up to set email alerts
|

A computational fluid dynamics investigation of the segmented integral squeeze film damper

Abstract: Rotor vibration attenuation is achieved with damping devices which work on different, often mutually coupled, physical principles. Squeeze film dampers are damping devices that have been widely used in rotordynamic applications. A new concept of a 5-segmented integral squeeze film damper, in which a flexure pivot tilting pad journal bearing is integrated, was investigated. The damper is studied for the eccentric position between the outer and inner ring of the squeeze film land. The ANSYS CFX software was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…where "k" is the stiffness coefficient of the ISFD, "n" is the number of loads, "Fi" is the radial load, and "Di" is the displacement of the ISFD under the load "Fi". Substituting the data in Figure 10 into Equation (17), the numerical analysis value of the ISFD stiffness coefficient is calculated to be 1.99 × 10 6 N/m and the experimental value is 2.01 × 10 6 N/m.…”
Section: Stiffness Properties Of Isfdmentioning
confidence: 99%
See 3 more Smart Citations
“…where "k" is the stiffness coefficient of the ISFD, "n" is the number of loads, "Fi" is the radial load, and "Di" is the displacement of the ISFD under the load "Fi". Substituting the data in Figure 10 into Equation (17), the numerical analysis value of the ISFD stiffness coefficient is calculated to be 1.99 × 10 6 N/m and the experimental value is 2.01 × 10 6 N/m.…”
Section: Stiffness Properties Of Isfdmentioning
confidence: 99%
“…γ" is the journal feed angular velocity. The numerical analysis value of ISFD damping coefficient can be calculated as 2.31 × 10 5 (N•s)/m by substituting the oil film force in Figure 11 into Equation (17). According to the results of the pressure cloud analysis obtained in Section 3.2, the oil film pressure obtained from the analysis is integrated, and the curve of the oil film force with time can be plotted, as shown in Figure 11.…”
Section: Damping Characteristics Of Isfdmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the temperature of the lubricant was observed to rise with increasing whirl speed and eccentricity ratios in SFD. Ferfecki et al [20] studied the pressure and velocity distribution of the segmented integral SFD. Their results showed that the supply pressure and the inertia of the oil had the influence on the pressure distribution and the hydraulic forces in the segmented integral SFD.…”
Section: Introductionmentioning
confidence: 99%